LcpB Is a Pyrophosphatase Responsible for Wall Teichoic Acid Synthesis and Virulence in Staphylococcus aureus Clinical Isolate ST59 - Pan, Ting; Guan, Jing; Li, Yujie; Sun, Baolin (Frontiers in Microbiology, 2021)
The community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) causes severe pandemics primarily consisting of skin and soft tissue infections. However, the underlying pathomechanisms of the bacterium are yet to fully understood. The present study identifies LcpB protein, which belongs to the LytR-CpsA-Psr (LCP) family, is crucial for cell wall synthesis and virulence in S. aureus. The findings revealed that LcpB is a pyrophosphatase responsible for wall teichoic acid synthesis. The results also showed that LcpB regulates enzyme activity through specific key arginine sites in its LCP domain. Furthermore, knockout of lcpB in the CA-MRSA isolate ST59 resulted in enhanced haemolytic activity, enlarged of abscesses, and increased leukocyte infiltration. Meanwhile, we also found that LcpB regulates virulence in agr-independent manner and the key sites for pyrophosphatase of LcpB play critical roles in regulating the virulence. In addition, the results showed that the role of LcpB was different between methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-sensitive Staphylococcus aureus (MSSA). This study therefore highlights the dual role of LcpB in cell wall synthesis and regulation of virulence. These insights on the underlying molecular mechanisms can thus guide the development of novel anti-infective strategies.